2014
DOI: 10.4103/2141-9248.139301
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analyses of the antimicrobial effect of ozonated water on supragingival plaque and salivary microbes

Abstract: Background:Ozone is an unstable gas, capable of oxidizing any biological entity. It is an effective bactericide in its gaseous as well as aqueous form.Aims:The objective of this study was to determine the in-situ antimicrobial effect of 0.1 ppm ozonated water on plaque and salivary microorganisms.Subjects and Methods:24 h old supragingival plaque (SP) was collected from the two most posterior teeth in the contralateral quadrants before and after a 30 s rinse with either distilled water (control group) or 0.1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Besides, the findings of this experiment demonstrated that ozone treatment of deep caries was associated with less need for RCT than conventional treatment. This could also be attributed to the fact that ozone is effective for killing cariogenic microorganisms [1][2][3][4][5]8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]29 . Also, ozone prevents formation of bacterial biofilms on dentine by changing dentine wettability through oxidation of organic elements (such as proteins, carbohydrates, glycolipids and acids) 8,12,17,30,31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the findings of this experiment demonstrated that ozone treatment of deep caries was associated with less need for RCT than conventional treatment. This could also be attributed to the fact that ozone is effective for killing cariogenic microorganisms [1][2][3][4][5]8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]29 . Also, ozone prevents formation of bacterial biofilms on dentine by changing dentine wettability through oxidation of organic elements (such as proteins, carbohydrates, glycolipids and acids) 8,12,17,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Caries management using ozone is conservative, consumes less treatment time, and requires shorter periods of mouth opening 11 . In addition, ozone is efficient in killing and reducing different cariogenic microorganisms (such as streptococcus mutans, streptococcus sobrinus and lactobacilli) in both clinical and laboratory settings, especially using the healozone [1][2][3][4][5]8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] .Previous studies established that ozone treatment using the healozone could enhance the remineralization process and thus improve the hardness of open single surface shallow carious lesions 4,7,28 . However, significantly less cariogenic microorganisms and more arrested caries were associated with ozone application into small shallow carious lesions but not in very deep large ones 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using hyper-ozonated solutions to cool surgical handpieces, piezo-electric and ablator handpieces, a more effective debridement of the bacterial biofilm 1 with a sharp reduction in the bacterial load of the surgical site. 3 In addition, there is a significant improvement in patient compliance and a much faster healing ( Figure 6). …”
Section: Preparation Of the Surgical Fieldmentioning
confidence: 98%
“…After extraction, curettage of the region is carried out, an abundant wash with hyper-ozonated water. 3 The surgical wound is sprinkled with ozonized paste. The surrounding tissues are infiltrated with low concentration ozone in order to promote restorative processes and blood supply.…”
Section: Treatment Of the Post-extractive Surgical Sitementioning
confidence: 99%